Enhancing Qur’anic Memorization Skills through Effective Learning Methods for Santri at Pesantren Assyifa - Ahmad Purkoni; Fabian Zaky Rabbani; Abdul Gofar; Tafsir Rozi (SocietalServe: Journal of Community Engagement and Services, 2025)
This community service program was designed to enhance Qur’anic memorization skills among santri at Pesantren Assyifa by integrating effective cognitive-based learning methods with traditional Islamic pedagogical practices. Conducted over eight weeks, the program involved initial assessments, teacher training, student workshops, practical memorization sessions, and structured evaluations. Modern memorization techniques—such as mnemonic devices, visualization, spaced repetition, and active recall—were introduced and practiced alongside classical methods like talaqqi and tikrar. The program targeted more than 40 santri and involved tahfiz teachers as active facilitators. Quantitative and qualitative assessments demonstrated notable improvement in memorization retention, engagement, and confidence. By the end of the program, over 85% of participants achieved measurable progress in both speed and accuracy of memorization. Feedback from students and teachers highlighted the usefulness and motivational impact of the techniques introduced. This program not only provided a fresh approach to Qur’anic learning but also offered sustainable strategies for long-term application within the pesantren. The success of the initiative supports the importance of combining Islamic values with contemporary educational insights to produce holistic and effective learning outcomes.